The study of causal link in a rare case of workplace injury - Massoni, Francesco; Tacconi, Maria Pia; Ricci, Lidia; D'Annibale, Colomba; Zaccheo, Alessandra; Barucca, Mauro (Acta Biomedica Atenei Parmensis, 2025)
We describe an episode of a displaced and comminuted fracture of a right-handed worker’s left scapula. The fracture was caused by a workplace injury in a factory. A negative anamnesis due to(for) direct trauma was reported. After a few minutes a violent contraction of his left shoulder, in the hospital the x-ray and computed tomography show a displaced and comminuted fracture of the left scapula. The description of the event and the clinical and instrumental picture find comfort in scientific literature, to which is necessary make appeal for the study of the causal link in the medical-examiner’s field in case of dynamics and rare lesions.